PYELOCALICEAL SYSTEM ANATOMICAL FACTORS FOR THE RESIDUAL FRAGMENTS CLEARANCE AFTER LOWER POLE STONES ESWL - Artyshchuk, V.; Vorobets, D.; Sheremeta, R.; Sheremeta, D.; Lychkovsky, O. (World of Medicine and Biology, 2016)
ESWL and PCNL effectivities after 45 and 90 days after fragmentation and extraction of lower pole kidney stones were established. Also, stones burden, lower infundibular length and width, lower infundibulopelvic and infundibulotransverse angles, stone free rate influences were evaluated. PCNL is more effective than ESWL at acute infundibulopelvic angle for stone free rate for 55,7% at 45 day and 33,3% at 90 day after operation. Complications and accessory procedures levels reminds the same but PCNL is associated with long operation period and less extended hospitalization staying. PCNL is more effective than ESWL at obtuse infundibulopelvic angle for stone free rate for 24,5% at 45 day and 0,9% at 90 day after operation with similar complication and accessory procedures rates.
Keywords: lower pole stone; infundibulopelvic angle; infundibultransverse angle